Epidemiological Investigation of Equine Influenza Virus Infection in Peninsular Malaysia - Abdul Hadi, Abdul Rahman D. (2009)
A cross-sectional study was conducted in Peninsular Malaysia with the objectives of determining the serological prevalence, molecular evidence and risk factors of equine influenza virus (EIV) distribution among different geographical regions. A total of 435 serum samples and 172 nasopharyngeal swabs were collected during July 2007-July 2008. Our study showed that the prevalence of antibodies against EIV was recorded in 215 of the 435 sera (49.4%). The prevalence of circulating antibodies against equine influenza virus in relation to states were recorded as; Selangor 127 out of 170 sera (74.7%) from vaccinated horses, and 9 out of 12 sera (75%) from unvaccinated horses, in Kelantan 37 out of 165 sera (22.4%) are unvaccinated horses, in Melaka 11 out of 25 sera (44%) are unvaccinated horses, in Negeri Sembilan 2 out of 23 sera (8.7%) are unvaccinated horses, in Johor 16 out of 17 sera (94.1%) are vaccinated horses, in Kedah 11 out of 14 sera (78.6%) are unvaccinated horses and in Pahang 2 out of 9 sera (22.2%) are vaccinated horses. The viral nucleic acid was detected in 77 of the 172 nasopharyngeal swabs (44.7%). The prevalence of positive nasopharyngeal swabs among vaccination status, were also recorded as, 44 out of 102 (43.1%) from vaccinated horses and 33 out of 70 (47.1 %) nasopharyngeal swabs from non-vaccinated horses. The association between several putative risk factors from vaccinated and unvaccinated groups on the seroconversion of equine influenza virus using binary logistic regression was recorded as; Age factor showed to be not significant factor in vaccinated groups against possible EIV infection as compared to unvaccinated groups which is recorded as 5.5 times chances to seroconverion. Thoroughbred groups showed a significant risk above unity whereas the pony groups breed showed a significant low risks. All others group of horses had non-significant, low risks. Sex did not contribute significantly to the epidemiology of the infection since there were no significant risk differences between sexes. This moderate antibody level detected from horses might indicate exposure of these animals to the virus or evidence of recent infection. The horses that were detected positive for equine influenza might be shedding the virus among naive population, and likely represent an important role in the epidemiology of respiratory disease outbreaks. In conclusion, the data presented in this study revealed that the ElV circulates among vaccinated and non-vaccinated horses in Malaysia and the incidence rate of EIV is relatively high. The periodic movement of sub-clinically infected horses at the international level provides the potential for interaction with susceptible populations and may serve as a crucial factor in transmission of infections among horse population. Absence of mandatory of vaccination program against EIV in Malaysia most probably contributed to the spread of the disease between provinces. Therefore, it is advisable to update equine influenza vaccine regularly.